Neuron‐specific expression of CuZnSOD prevents the loss of muscle mass and function that occurs in homozygous CuZnSOD‐knockout mice. Issue 4 (30th December 2013) - Sakellariou, Giorgos K.; Davis, Carol S.; Shi, Yun; Ivannikov, Maxim V.; Zhang, Yiqiang; Vasilaki, Aphrodite; Macleod, Gregory T.; Richardson, Arlan; Van Remmen, Holly; Jackson, Malcolm J.; McArdle, Anne; Brooks, Susan V.
Abstract : Deletion of copper‐zinc superoxide dismutase (CuZnSOD) in Sod1 –/– mice leads to accelerated loss of muscle mass and force during aging, but the losses do not occur with muscle‐specific deletion of CuZnSOD. To determine the role of motor neurons in the muscle decline, we generated transgenic Sod1 –/– mice in which CuZnSOD was expressed under control of the synapsin 1 promoter ( SynTgSod1 –/– mice). SynTgSod1 –/– mice expressed CuZnSOD in brain, spinal cord, and peripheral nerve, but not in other tissues. Sciatic nerve CuZnSOD content in SynTgSod1 –/– mice was 20% that of control mice, but no reduction in muscle mass or isometric force was observed in SynTg‐Sod1 –/– mice compared with control animals, whereas muscles of age‐matched Sod1 –/– mice displayed 30–40% reductions in mass and force. In addition, increased oxidative damage and adaptations in stress responses observed in muscles of Sod1 –/– mice were absent in SynTgSod1 –/– mice, and degeneration of neuromuscular junction (NMJ) structure and function occurred in Sod1 –/– mice but not in SynTgSod1 –/– mice. Our data demonstrate that specific CuZnSOD expression in neurons is sufficient to preserve NMJ and skeletal muscle structure and function in Sod1 –/– mice and suggest that redox homeostasis in motor neurons plays a key role in initiating sarcopenia during aging.—Sakellariou, G. K., Davis, C. S., Shi, Y., Ivannikov, M. V., Zhang, Y., Vasilaki, A., Macleod, G. T., Richardson, A., Van Remmen, H., Jackson, M. J., McArdle, A., Brooks, S. V. Neuron‐specific expression of CuZnSOD prevents the loss of muscle mass and function that occurs in homozygous CuZnSOD‐knockout mice. FASEB J. 28, 1666‐1681 (2014). www.fasebj.org